2013
DOI: 10.1016/j.nicl.2013.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of brain derived neurotrophic factor influences β amyloid load in cognitively intact apolipoprotein E ε4 carriers

Abstract: Aside from apolipoprotein E (APOE), genetic risk factors for β amyloid deposition in cognitively intact individuals remain to be identified. Brain derived neurotrophic factor (BDNF) modulates neural plasticity, which has been implicated in Alzheimer's disease. We examined in cognitively normal older adults whether the BDNF codon 66 polymorphism affects β amyloid burden and the relationship between β amyloid burden and cognitive scores, and how this relates to the effect of APOE. Amyloid load was measured by me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 77 publications
0
69
0
Order By: Relevance
“…37 Other groups have noted similar moderating effects of Ab and BDNF on cognition in older adults. 38 This interaction between Ab and the BDNF Val66Met polymorphism adds further support for the potential role the BDNF protein has in moderating Ab production, thus protecting cognitive function. Animal studies have indicated that BDNF regulates sorting protein-related receptor with A-type repeats, a known modulator of Ab precursor protein trafficking and processing, via extracellular signalregulated protein kinase stimulation, suggesting that BDNF could deter amyloid production.…”
Section: C-pittsburgh Compound B-pet Neuroimaging Protocolmentioning
confidence: 82%
“…37 Other groups have noted similar moderating effects of Ab and BDNF on cognition in older adults. 38 This interaction between Ab and the BDNF Val66Met polymorphism adds further support for the potential role the BDNF protein has in moderating Ab production, thus protecting cognitive function. Animal studies have indicated that BDNF regulates sorting protein-related receptor with A-type repeats, a known modulator of Ab precursor protein trafficking and processing, via extracellular signalregulated protein kinase stimulation, suggesting that BDNF could deter amyloid production.…”
Section: C-pittsburgh Compound B-pet Neuroimaging Protocolmentioning
confidence: 82%
“…All participants gave written informed consent that was approved by the Internal Review Board of each participating institution. We grouped subjects into 3 cohorts: an autopsy cohort (n 5 68) comprising terminally ill patients with subsequent postmortem confirmation of brain amyloid status; a test cohort (n 5 172) comprising 33 patients with clinically probable Alzheimer disease, 80 patients with mild cognitive impairment, and 59 healthy volunteers; and a healthy cohort comprising 105 healthy volunteers from 3 studies (7,13,14).…”
Section: Subjects and Imagingmentioning
confidence: 99%
“…Inclusion was stratified for two genetic factors: BDNF ! 5 (met allele present or absent) and APOE (ε4 allele present or absent), as this cohort was part of a larger 18 F-flutemetamol study in healthy controls of the interactions between these polymorphisms [16,17] frames were realigned and summed for both data sets separately. The individual's 18 Fflutemetamol and 11 C-PIB PET summed images were co-registered to the subject's T1-weighted structural MRI.…”
Section: Participantsmentioning
confidence: 99%
“…The spatially standardised volumes of interest (VOIs) were identical for 18 Fflutemetamol and for 11 C-PIB image analysis. The cerebellar GM was defined based on the automated anatomical labelling (AAL) atlas (areas 91-108) and masked inclusively with subjectspecific GM maps, with the threshold for masking set at > 0.3 [16,17]. This reference region was used both for 18 F-flutemetamol and for 11 C-PIB images.…”
Section: Semiquantitative Analysis Of Amyloid Petmentioning
confidence: 99%